2006
DOI: 10.1038/nature05363
|View full text |Cite
|
Sign up to set email alerts
|

Polyadenylation factor CPSF-73 is the pre-mRNA 3'-end-processing endonuclease

Abstract: Most eukaryotic messenger RNA precursors (pre-mRNAs) undergo extensive maturational processing, including 3'-end cleavage and polyadenylation [1][2][3][4][5][6][7][8] . Despite the characterization of a large number of proteins that are required for the cleavage reaction, the identity of the endoribonuclease is not known 4,9,10 . Recent analyses suggested that the 73 kD subunit of cleavage and polyadenylation specificity factor (CPSF-73) may be the endonuclease for this and related reactions [10][11][12][13][1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
524
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 409 publications
(554 citation statements)
references
References 31 publications
(39 reference statements)
24
524
1
Order By: Relevance
“…The crystal structure of the metallo-β-lactamase and β-CASP domains of Cft2p/Ydh1p was reported recently [112]. The overall structure is similar to that of CPSF-73 (Fig.…”
Section: Cpsf-100 (Cft2p/ydh1p)supporting
confidence: 59%
See 2 more Smart Citations
“…The crystal structure of the metallo-β-lactamase and β-CASP domains of Cft2p/Ydh1p was reported recently [112]. The overall structure is similar to that of CPSF-73 (Fig.…”
Section: Cpsf-100 (Cft2p/ydh1p)supporting
confidence: 59%
“…Biochemical studies with the bacterially expressed and purified human CPSF-73 showed that it possessed weak ribonuclease activity towards pre-mRNA substrates [112], in the absence of the other proteins of the 3′-end processing machinery. This activity was enhanced greatly when the purified protein was pre-incubated with Ca 2+ ions.…”
Section: Cpsf-73 (Brr5p/ysh1p)mentioning
confidence: 99%
See 1 more Smart Citation
“…The former is bound by the cleavage and polyadenylation specificity factor (CPSF) complex and the latter by cleavage stimulation factors (CstF). The RNA is then cut by CPSF73 [3], whereupon the coding portion is polyadenylated and the 3ʹ product rapidly degraded. The central role of the PAS in termination provides the premise for two potential mechanisms.…”
Section: Overviewmentioning
confidence: 99%
“…The b-CASP domain, which is always appended to a metallo-blactamase domain, is strictly required for Artemis function (Poinsignon et al, 2004b). The three-dimensional structure of several RNA-specific b-CASP members has recently revealed the general organization of these proteins into two domains: a metallo-b-lactamase domain and a b-CASP domain, with the active site being located at the interface between the two domains (Ishikawa et al, 2006;Mandel et al, 2006). Several Serine residues, mostly located in the C-terminus half of the protein, have been identified in vitro and in vivo as targets of phosphatidylinositol 3-kinase like kinases, including DNA-PKcs (Poinsignon et al, 2004a; Riballo et al, 2004;Zhang et al, 2004;Chen et al, 2005;Ma et al, 2005;Wang et al, 2005b;Goodarzi et al, 2006;Soubeyrand et al, 2006).…”
Section: Artemismentioning
confidence: 99%